Prevalence of self-medication among people in a pharmacy in the countryside of Paraná (Research, Society and Development, 2022)
Self-medication represents the indiscriminate use of medicines without guidance or supervision from a qualified professional. Medicines are essential for health, contributing to the treatment of countless pathologies when used rationally. Thus, the objective of this article is to analyze the prevalence in which self-medication occurs, verifying the most used drugs. For this, a survey was carried out descriptive and quantitative research was carried out through the analysis of data collected in a questionnaire applied in a private pharmacy, located in the western region of Paraná. A total of 50 questionnaires were completed, the largest number of participants was female, 28 (56%), while 22 (44%) were male. With regard to self-medication due to influences, the fact that participants had the medication at home, 21 (42%), was highlighted, followed by the leftover medication due to incomplete treatment 19 (38%), equated with indications from family and friends, and finally, the media totaling 3 (6%). Regarding the health problems that led to self-medication, the lowest rate was for back pain with 11 people (22%) and the highest, for headaches, 37 people (74%). As for the most used drugs, dipyrone stood out, with 36 people using it (72%) and paracetamol, with 32 people (64%). Self-medication was common in the population studied due to the ease of access and numerous influencing factors.